Induction of amphotericin B resistance in susceptible Candida auris by extracellular vesicles. Issue 1 (31st December 2022) - Chan, Walton; Chow, Franklin Wang-Ngai; Tsang, Chi-Ching; Liu, Xueyan; Yao, Weiming; Chan, Tony Tat-Yin; Siu, Gilman Kit-Hang; Ho, Alex Yat-Man; Luk, Kristine Shik; Lau, Susanna Kar-Pui; Woo, Patrick Chiu-Yat
ABSTRACT: Drug resistance derived from extracellular vesicles (EVs) is an increasingly important research area but has seldom been described regarding fungal pathogens. Here, we characterized EVs derived from a triazole-resistant but amphotericin B-susceptible strain of Candida auris . Nano- to microgram concentrations of C. auris EVs prepared from both broth and solid agar cultures could robustly increase the yeast's survival against both pure and clinical amphotericin B formulations in a dose-dependent manner, resulting in up to 16-fold changes of minimum inhibitory concentration. Meanwhile, this effect was not observed upon addition of these EVs to C. albicans, nor upon addition of C. albicans EVs to C. auris . No change in susceptibilities was observed upon EV treatment for fluconazole, voriconazole, micafungin, and flucytosine. Mass spectrometry indicated the presence of immunogenic-/drug resistance-implicated proteins in C. auris EVs, including alcohol dehydrogenase 1 as well as C. albicans Mp65-like and Xog1-like proteins in high quantities. Based on these observations, we propose a potential species-specific role for EVs in amphotericin B resistance in C. auris . These observations may provide critical insights into treatment of multidrug-resistant C. auris .